Directional filter bank: An enhancement for fingerprint feature detection - Tantachun, S.; Pintavirooj, C.; Sangworasil, M.; Kitjaidure, Y. (My University, 2006)
Fingerprints is the most popular biometric modality. Fingerprint features include core, delta, ridge bifurcation, ridge ending, enclosure and short edge. In order to increase the performance of fingerprint identification system, it is essential that these directional-related features are needed to be enhanced. In this paper, we purpose the directional filter bank to enhance the fingerprint features which later used in classification step. Our 2D FIR filter is designed using a 2D frequency-transform method which is easily implemented and easily imposed a zero phase response. Our proposed technique demonstrates the promising results. © 2006 IEEE.
Keywords: Biometric; Directional filter bank; Fingerprint